Offline Shopping Behavior during the COVID-19 Pandemic - Aamir Khan; Sukardi (The Indonesian Institute of Science and Technology Research, 2023)
During the COVID-19 pandemic, by maintaining health protocols, young people and community members continue to shop to meet daily needs, especially food needs, both online and offline shopping. This study aims to explain the effect of wearing masks, maintaining distance and washing hands-on offline shopping behaviour. The population of this study was young people in Indonesia. There were 155 respondents from various regions. The sampling technique used is a random sampling area. The sample is based on regionality by not comparing the proportionality of the site. The results showed that using masks had a significant positive effect on offline shopping behaviour. Social distance has a significant negative impact on offline shopping behaviour. Handwashing does not affect offline shopping behaviour.